Escalating global exposure to compound heat-humidity extremes with warming. (19th May 2020) - Li, Dawei; Yuan, Jiacan; Kopp, Robert E
Abstract: Heat stress harms human health, agriculture, the economy, and the environment more broadly. Exposure to heat stress is increasing with rising global temperatures. While most studies assessing future heat stress have focused on surface air temperature, compound extremes of heat and humidity are key drivers of heat stress. Here, we use atmospheric reanalysis data and a large initial-condition ensemble of global climate model simulations to evaluate future changes in daily compound heat-humidity extremes as a function of increasing global-mean surface air temperature (GSAT). The changing frequency of heat-humidity extremes, measured using wet bulb globe temperature (WBGT), is strongly related to GSAT and, conditional upon GSAT, nearly independent of forcing pathway. The historical ∼1°C of GSAT increase above preindustrial levels has already increased the population annually exposed to at least one day with WBGT exceeding 33°C (the reference safety value for humans at rest per the ISO-7243 standard) from 97 million to 275 million. Maintaining the current population distribution, this exposure is projected to increase to 508 million with 1.5°C of warming, 789 million with 2.0°C of warming, and 1.22 billion with 3.0°C of warming (similar to late-century warming projected based on current mitigation policies).